Prospective cohort study protocol to describe the transfer of patients from intensive care units to hospital wards. Issue 7 (8th July 2015) - Buchner, Denise L; Bagshaw, Sean M; Dodek, Peter; Forster, Alan J; Fowler, Robert A; Lamontagne, François; Turgeon, Alexis F; Potestio, Melissa; Stelfox, Henry T
Abstract : Introduction: The transfer of patient care between the intensive care unit (ICU) and the hospital ward is associated with increased risk of medical error and adverse events. This study will describe patient transfer from ICU to hospital ward by documenting (1) patient, family and provider experiences related to ICU transfer, (2) communication between stakeholders involved in ICU transfer, (3) adverse events that follow ICU transfer and (4) opportunities to improve ICU to hospital ward transfer. Methods: This is a mixed methods prospective observational study of ICU to hospital ward transfer practices in 10 ICUs across Canada. We will recruit 50 patients at each site (n=500) who are transferred from ICU to hospital ward, and distribute surveys to enrolled patients, family members, and healthcare providers (ICU and ward physicians and nurses) after patient transfer. A random sample of 6 consenting study participants (patients, family members, healthcare providers) from each study site (n=60) will be offered an opportunity to participate in interviews to further describe stakeholders' experience with ICU to hospital ward transfer. We will abstract information from patient health records to identify clinical data and use of transfer tools, and identify adverse events that are related to the transfer. Ethics and Dissemination: Research ethics board approval has been obtained at the coordinating study centre (UofC REB13-0021) and 5 study sites (UofA Pro00050646; UBC-PHC H14-01667; Sunnybrook 336-2014; QCH 14-07; Sherbrooke 14-172). Dissemination of the findings will provide a comprehensive description of transfer from ICU to hospital ward in Canada including the uptake of validated or local transfer tools, a conceptual framework of the experiences and needs of stakeholders in the ICU transfer process, a summary of adverse events experienced by patients after transfer from ICU to hospital ward, and opportunities to guide quality improvement efforts.